Analysis of the Application of Financial Management Principles to Mosque Financial Reports in Sinjai Regency - Ainun Nabilai; Mutiara Ramadani; Nurdiana; Muh Irsan Irwanto; Sitti Hadija; Sindy Gusliana; Muttiarni (JEKAMI Journal of Accounting, 2024)
One of the most important aspects in maintaining the survival and prosperity of a mosque is good financial management. The reason is, mosques also require quite a bit of monthly funds.  The aim of this research is to determine the accountability and transparency of mosque financial reports. The research method is qualitative with 12 informants who are mosque managers and congregation members of the Raya Nur Balangnipa Mosque. Qualitative data relating to the research subject was collected through distributing questionnaires.  Primary and secondary data are the data sources used in this research for data collection.   Based on the research results, it was found that the implementation of financial report management at the Nur Balangnipa Grand Mosque in Sinjai district apparently used manual or basic techniques.  Mosques only keep financial records of money coming in, money going out and the final balance.    Then, once a week, before prayer, the mosque's microphone is used to announce money coming in, money going out, and the final cash balance.  In addition, for non-benefit financial reports, targeted investigations show that the financial reports of non-benefit associations have not prepared financial reports in accordance with existing principles, especially PSAK No. 45 means that the mosque administrators do not know and do not understand PSAK no. 45